Gestão ambiental em escolas de negócios: mapeando o estado-da-arte - Jabbour, Charbel José Chiappetta [UNESP] (Departamento de Empreendedorismo e Gestao da UFF, 2014)
Following the guidelines of the United Nations, which established the Decade of Education for Sustainable Development (2005-2014) and the Principles for Responsible Management Education (PRME), the pressure on business schools for incorporating environmental management in their core activities (teaching, research, extension and university management) have intensified. In contrast, in Brazil, this discussion is still embryonic, and in some cases, the Business Schools seem to be in latter than the environmental management practiced by the world-class companies in the industrial sector. Therefore, this article prospected and systematized the state of the art on the inclusion of environmental management issues in the activities of Business Schools, by mapping the territory of the main academic works in this subject. The main results indicate that the state of the art is represented by: a vibrant leadership of U.S. researchers and others developed countries, a clear analytical reductionism of research, mainly by focusing on the dimension "teaching" does not addressing a systemic perspective that encompasses environmental management in the range of typical activities of Business Schools, a significant predominance of theoretical studies on the subject and a consequent lack of empirical studies, mainly based on multiple cases.

Após as diretrizes da Organização das Nações Unidas, que instituíram a Década da Educação para o Ensino de Desenvolvimento Sustentável (2005-2014) e o lançamento dos Principles for a Responsible Management Education (PRME), a pressão para que as Escolas de Negócios/Gestão incorporem a gestão ambiental em suas atividades essenciais (ensino, pesquisa, extensão e gestão universitária) se intensificaram. Em contrapartida, no Brasil, essa discussão é ainda embrionária, e, em alguns casos, as Escolas de Negócios parecem estar em descompasso com a gestão ambiental praticada pelas empresas classe-mundial do setor industrial. Por isso, neste artigo é prospectado e sistematizado o estado-da-arte sobre a inclusão da temática ambiental nas atividades das Escolas de Negócios, mapeando-se o território das principais obras do tema. Os principais resultados indicam que no estado-da-arte vigora: uma pujante liderança de pesquisadores estadunidenses e de outros países desenvolvidos na temática; um evidente reducionismo analítico das pesquisas, ao enfocarem principalmente a dimensão “ensino”, não abordando uma perspectiva sistêmica que englobe a gestão ambiental no conjunto de atividades típicas das Escolas de Negócios; uma significativa predominância de estudos teóricos sobre o tema e uma consequente carência de estudos teórico-empíricos, principalmente de estudo de múltiplos casos.
Environmental management in business schools: mapping the state of the art
Keywords: Environmental management; Business schools; State of the art; Gestão ambiental; Escolas de negócios; Sustentabilidade; Estado da arte